Le Management Des Connaissances Au Niveau Des Etablissements D’enseignement Superieur : Cas Des Universites Publiques Marocaines - Abdelilah Elkharraz; Ouail El Kharraz; Khalid Chafik (European Scientific Journal, ESJ, 2018)
This study aims to answer questions on the place, the role and the impact of the knowledge management to improve and develop the Moroccan university. The research is mainly based on an empirical study carried out on the implementation status of the knowledge management in eight Moroccan universities. The obtained answers show important results not only theoretically but also, and especially, empirically. The conducted study is based on a qualitative approach characterized by a descriptive analysis of the current state by referring to the technique of semistructured interviews with different officials at the presidency level in these universities. Despite the absence of a strategy formalised by the knowledge management within these universities, the analysis of the data collected shows that these practices have a positive effect on improving the quality of learning and, when making decisions, factors like the dominant culture, the socio-technical state and the decentralisation play a crucial role in adopting strategies based on the knowledge management